2022
DOI: 10.29036/jots.v13i24.366
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Value, Inter-functional Coordination, and Strategic Adaptation: The Perspective on Selecting Travel Agencies from School Travel Plan

Abstract: School travel plan (STP) is a significant tourism market for travel agencies; this study explores how travel agencies with customer orientation ability, product advantages, and high-quality service performance affect customer perceived value and the strategic adaptation of travel agencies from a resource-based view by moderating the effect of inter-functional coordination. Proportionate stratified sampling was used to select teachers and administrators from junior and high schools who participated in graduatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…This study designed and validated our measures as suggested by MacKenzie et al (2011) with four items of strategic adaptation modified from Kan (2022), customer service ability scales adopted from Sok et al (2018), compatibility with three items adopted by Wu (2022), relational ties with five items operationalized based on Huo et al (2022), technological capabilities with five items adapted from Ku (2014) and joint decision-making scales modified from Kim et al (2023). Finally, three items modified product development efficiency (Ku et al , 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study designed and validated our measures as suggested by MacKenzie et al (2011) with four items of strategic adaptation modified from Kan (2022), customer service ability scales adopted from Sok et al (2018), compatibility with three items adopted by Wu (2022), relational ties with five items operationalized based on Huo et al (2022), technological capabilities with five items adapted from Ku (2014) and joint decision-making scales modified from Kim et al (2023). Finally, three items modified product development efficiency (Ku et al , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Strategic adaptation refers to an organization’s ability to optimize and adapt to its strategy during technological disruptions (Kan, 2022). AI within data-driven approaches is emerging as an attractive solution for planners (Cipi et al , 2023) and consumers to make more informed decisions about its adoption.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rehman and Anwar (2019) perceive risk management from the perspective of the need for more effective strategies in SMEs. According to Kan (2022), inter-functional coordination has a moderating effect on customer perceived value and company's strategic adaptation. SMEs face higher risks in terms of globalization resulting from their limited resources and small size.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Different from operational risk management, strategic risk management is a long-term decision-making process that stimulates business development on a long-term basis (Fudaliński, 2015). The coordination of firms' departments regarding firms' objectives will also increase the strategic adaptation of enterprises (Kan, 2022). Firms implementing aggressive strategic risk management practices receive competitive advantages and are successful in product development and accessing new markets.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%